APPLICATIONS OF SHIROABHYANGA (HEAD MASSAGE) AND IT’S ROLE IN THE MANAGEMENT OF DARUNAKA (DANDRUFF) – A SCIENTIFIC REVIEW (AYUSHDHARA, 2021)
Darunaka, considered as dandruff is a Kapalagata and a Shirogata roga that commonly affects today’s young generation because of their modified lifestyles, improper dietary habits, improper maintenance of hair, use of various chemical included hair products and due to high stress at the workplace. Due to the advancement of many new hair products, people hardly remember the application of hair oil, also called as Shiroabhyanga, ancient practice for maintaining the hair and keeping the mind cool. Modernization has lead to lack of these practices and a rise in the disorders of hair including stress. There are many studies are available on the scalp disease Darunaka and the application of Shiroabhyanga with specific oils. In this study an effort has been made to review all such studies that involve the Darunaka and Shiroabhyanga or the head massage or the application of oil and to evaluate the probable mode of action of the same which would be very helpful for the researchers, practitioners and Ayurvedic fraternity to validate the procedure of Shiroabhyanga and its applicability in the present health disorders that are caused due to excessive stress. This study might also give an idea to the novice researchers for incorporating an Ayurvedic therapy like Shiroabhyanga along with Yoga and other systems of medicine in reducing the complaints of the patient and serving the society for the better.